Creative Writing - Sandnes, Charmaine Henrietta (My University, 2007)
In this Theoretical Introduction the reasons for the choice of the historical fiction genre for the creative component of this Research Report will become clear in relation to other notable examples of the genre, indeed the academic essay will revolve around primary concerns with regard to the narrative of historical fiction and the debates around the representation that the work engages. In the postscript to the academic essay the possible destination for publication will be considered, as well as a summation of the writing and revision process, and a rumination of the projected readership or audience. As the creative component will be submitted in partial form, the postscript to the theoretical introduction will extrapolate the rest of the project, so as to provide some sense of the intended eventual work. Finally a special thanks to Ashleigh Harris, whose untiring help and encouragement is deeply appreciated; and to my husband, Norman, whose concern and enormous patience has sustained this endeavour.
Student Number : 0420532W - MA research report - School of Literature and Language Studies - Faculty of Humanities
Keywords: historical fiction; genre; narrative; academic essay